2023
DOI: 10.1038/s41598-023-31939-4
|View full text |Cite
|
Sign up to set email alerts
|

A fish-parasite sentinel system in an assessment of the spatial distribution of polychlorinated biphenyls

Abstract: The spatial distribution of polychlorinated biphenyls (PCBs), in the Zemplínska Šírava water reservoir and adjacent tributaries in the Bodrog River Basin were investigated using a fish-parasite sentinel system. PCB concentrations were detected in various fish matrices (dorsal and abdominal muscles, liver and intestine) of the Wels catfish (Silurus glanis) and its intestinal cestode Glanitaenia osculata. PCB concentrations in the fish from the water reservoir, located closest to the chemical plant, the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The examined specimens of A. lucii came from perch (Perca fluviatilis) caught in three localities differing in their degree of environmental pollution. The first was the heavily PCB-polluted Zemplínska Šírava (ZŠ) reservoir (48 • 47 ′ 09.0" N 21 • 57 ′ 20.5" E), the second was the Laborec River (LB) (48 • 31 ′ 20.7" N 21 • 54 ′ 17.5" E), which is connected to the ZŠ reservoir (detailed information and a map of these two sites can be found in [7]), and the third, which was defined as an unpolluted reference site, was a small unpolluted pond near the eastern Slovakian village of Pozdišovce (PZ) (48 A total of 91 worms were collected from three populations: 68 A. lucii individuals, including 33 males and 35 females, were collected from fish from ZŠ, 19 individuals, including 12 males and 7 females, from LB and 4 individuals, including 3 males and 1 female, from PZ. All individual parasites were rinsed in 0.9% saline solution immediately after isolation from the intestine of the fish host and identified microscopically by counting the hooks and hook rows and by the shape of the proboscis hook roots [32].…”
Section: Study Sites and Parasite Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The examined specimens of A. lucii came from perch (Perca fluviatilis) caught in three localities differing in their degree of environmental pollution. The first was the heavily PCB-polluted Zemplínska Šírava (ZŠ) reservoir (48 • 47 ′ 09.0" N 21 • 57 ′ 20.5" E), the second was the Laborec River (LB) (48 • 31 ′ 20.7" N 21 • 54 ′ 17.5" E), which is connected to the ZŠ reservoir (detailed information and a map of these two sites can be found in [7]), and the third, which was defined as an unpolluted reference site, was a small unpolluted pond near the eastern Slovakian village of Pozdišovce (PZ) (48 A total of 91 worms were collected from three populations: 68 A. lucii individuals, including 33 males and 35 females, were collected from fish from ZŠ, 19 individuals, including 12 males and 7 females, from LB and 4 individuals, including 3 males and 1 female, from PZ. All individual parasites were rinsed in 0.9% saline solution immediately after isolation from the intestine of the fish host and identified microscopically by counting the hooks and hook rows and by the shape of the proboscis hook roots [32].…”
Section: Study Sites and Parasite Collectionmentioning
confidence: 99%
“…Numerous ecotoxicological studies conducted over the past two decades have documented a link between environmental pollution and parasitism, particularly with regard to the use of parasites as indicators of environmental health [2]. A number of studies have demonstrated the ability of various endoparasite taxa to take up toxic heavy metals [3,4] and organic pollutants such as persistent PCBs [5][6][7] from their hosts. Cestodes and acanthocephalans in particular can accumulate pollutants at levels far above those found in the muscles of their hosts, thus greatly benefiting hosts by reducing chemical exposure and detoxification [8].…”
Section: Introductionmentioning
confidence: 99%